2015
DOI: 10.1007/s00430-015-0419-9
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 subtypes and drug resistance profiles in a cohort of heterosexual patients in Istanbul, Turkey

Abstract: Turkey is seeing a steady rise in rates of HIV infection in the country. The number of individuals with HIV/AIDS was greater than 7000 in 2014 according to data released by the Ministry of Health, and heterosexual contacts were reported to be the main transmission routes. Istanbul has the highest number of reported cases of HIV infection. The aim of the study was to determine the prevalence of HIV-1 drug resistance in 50 heterosexual patients from Istanbul. The most prevalent subtype was found to be subtype B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…In prior studies, HIV was reported in 6.7%-15.1% of patients (15,27). Although the HIV infection rate has increased in recent decades, the overall HIV prevalence is still low compared with that in Western countries (28)(29)(30). This discrepancy may be due to the low prevalence of HIV in general (7,29).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In prior studies, HIV was reported in 6.7%-15.1% of patients (15,27). Although the HIV infection rate has increased in recent decades, the overall HIV prevalence is still low compared with that in Western countries (28)(29)(30). This discrepancy may be due to the low prevalence of HIV in general (7,29).…”
Section: Discussionmentioning
confidence: 96%
“…Although the HIV infection rate has increased in recent decades, the overall HIV prevalence is still low compared with that in Western countries (28)(29)(30). This discrepancy may be due to the low prevalence of HIV in general (7,29). There is no national screening program for anal cancer and anal precancerous lesions in HIV-positive patients.…”
Section: Discussionmentioning
confidence: 99%